2015
DOI: 10.1007/s13277-015-3465-4
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA CCHE1 promotes cervical cancer cell proliferation via upregulating PCNA

Abstract: Long noncoding RNAs (lncRNAs) have been shown to play important roles in carcinogenesis and progression. However, the roles and functional mechanisms of lncRNAs in cervical cancer remain largely unknown. In this study, we found that cervical carcinoma high-expressed lncRNA 1 (lncRNA-CCHE1) was significantly upregulated in cervical cancer tissues. The higher expression of CCHE1 was significantly correlated with large tumor size, advanced Federation of Gynecology and Obstetrics stage, uterine corpus invasion, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 35 publications
5
92
1
Order By: Relevance
“…lncRNAs constitute a heterogeneous group of RNA molecules in eukaryotic cells and play a role in a wide variety of biological processes (Hanahan and Weinberg 2000). Previous studies have shown that expression of several lncRNAs is dysregulated in cancer tissues, such as MEG3 (Luo et al 2015), CCHE1 (Yang et al 2015), and HOTAIR (Ding et al 2015). In the present study, high levels of Loc554202 were observed in cervical cancer tissues compared with the surrounding non-tumor cervical tissues.…”
Section: Discussionsupporting
confidence: 51%
“…lncRNAs constitute a heterogeneous group of RNA molecules in eukaryotic cells and play a role in a wide variety of biological processes (Hanahan and Weinberg 2000). Previous studies have shown that expression of several lncRNAs is dysregulated in cancer tissues, such as MEG3 (Luo et al 2015), CCHE1 (Yang et al 2015), and HOTAIR (Ding et al 2015). In the present study, high levels of Loc554202 were observed in cervical cancer tissues compared with the surrounding non-tumor cervical tissues.…”
Section: Discussionsupporting
confidence: 51%
“…However, many recent studies have examined the roles of various lncRNAs in cancer; examples include MALAT1 in small cell lung carcinoma [38, 39], lncRNA-ATB in hepatocellular carcinoma, and NKILA in breast cancer [40, 41]. Many lncRNAs also participate in the progression of cervical cancer, affecting proliferation, apoptosis, metastasis, radio-resistance, and HPV [4244]. Many potentially cancer-relevant lncRNAs have not yet been characterized, and future lncRNA studies may help greatly improve individualized diagnosis techniques [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs may exert their biological functions via regulating expression of cancer-associated genes in transcriptional level or post-transcriptional level [33][34][35][36]. However, LET has been reported to bind and downregulate nuclear factor 90 protein abundance in hepatocellular carcinoma [21].…”
Section: Discussionmentioning
confidence: 99%